Esophagoduodenal Varices in Non-cirrhotic Portal Hypertension with Myelodysplastic Syndrome: A Case Report - Ina Rosalina; Reza Latumahina; Yudith Setiati Ermaya; Dwi Prasetyo (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Esophagogastroduodenal varices are dilated submucosal of distal esophageal, gastric, and duodenal veins connecting the portal and systemic circulation. This case report aims to describe a unique case of a child with esophagoduodenal varices due to myelodysplastic syndrome. Case: We reported a case of 3-year-old girl who came to Hasan Sadikin General Hospital on April 3 2022, complaining of black stools 1 time per day for two days before admission. She had previously been diagnosed with esophagogastroduodenal varices since 2019. On initial examination, the patient was fully conscious and appeared pale. The patient's clinical condition improved after adequate treatment of blood transfusion, octreotide, omeprazole and propanolol. However, patient later developed pancytopenia and underwent bone marrow puncture examination which revealed a myelodysplastic syndrome. Discussion: Myelodysplastic syndrome is a condition where ineffective hematopoiesis occurs and can lead to blood malignancy, especially acute myeloblastic leukemia. In this patient, she presented with unequivocal hypertensive gastroesophageal varices, splenomegaly, absence of fibrosis and thrombocytosis supporting subsequent diagnosis of idiopathic non cirrhosis portal hypertension. On the other hand, non-cirrhotic portal hypertension can also be caused by myelodysplastic syndrome as described in this case report. Conclusion: Myeloproliferative malignancies can be a cause of idiopathic non cirrhosis portal hypertension. Pancytopenia often occurs in patients with portal hypertension due to splenomegaly or myelodysplastic syndrome, which can lead to acute myeloblastic leukemia, an example of a myeloproliferative malignancy.